Fenomena Pornoteks Di Kolom Komentar Selebriti Instagram @SARAHVILO.ID Sebagai Masalah Sosial Pada Media Baru - Shinta Hartini Putri; Leoni Oktavia Maharani (ArtComm, 2020)
Social media, especially Instagram, has become one of the means to explore and express themselves. Instagram presents interactive features in facilitating its users, but not all Instagram users are wise and obey ethics in communicating on social media. This happened to Sarah Viloid's Selebgram account, which has millions of followers, after rising followers of Sarah, pornographic comments began to appear and are increasingly being found in almost every photo post of Sarah. Surely these comments will create discomfort, both for Sarah as the account owner, and for other Instagram users who read these obscene comments. This study uses descriptive qualitative research methods, with primary data collection techniques through observation based on Instagram user comments on Sarah Viloid photo uploads, while secondary data uses library research, journals, and internet sources. Data analysis used by the Miles and Huberman models and triangulation for data validity techniques. This research output will be published in the journal of the Faculty of Communication and Design UNIBI.